What Is Leadership? / Nur lliana Baharudin Shah - Baharudin Shah, Nur lliana (2014)
What does it mean to be a leader? Is it the title of President, Chairman, General etc? To me, it's more than that No doubt about that where title are important, but they don't have much value when it comes to leading. True leadership cannot be awarded, appointed or assigned. However, it is also true that people who are awarded, appointed or assigned leadership positions, have a key role to play in society, and if true leadership is not within them, then at least some effort is needed to build their leadership capacity or else the teams they lead are doomed. Therefore, in leadership there are traits of leaderships which are having exemplary characteristic, passionate, confident, good leadership and tolerance.